Mapping the Research Landscape of Interpreter and Translator Education : Current Themes and Future Directions - Li, Xiangdong (London : Routledge, 2025)
Mapping the Research Landscape of Interpreter and Translator Education explores research themes in interpreter and translator education based on a systematic review of more than20 years of research in the field. The book focuses on the ten research themes on the chain of curriculum development and evaluation, specifically, market needs analysis, content conceptualisation, learning needs analysis, teaching objectives, teaching beliefs, syllabus design, material development, instruction and/or effect, assessment, and course evaluation. It also touches upon the other14 research themes, for example, trainer education, admissions, learner traits, thesis and research training, pre-service preparation, certification, in-service training, client education, and translation and interpreting as a means to education. The discussion of each theme is accompanied by a synthesis of its sub-themes, typical research cases, research prospects, and suggested reading. As a guide, it supports teachers by illustrating how to combine teaching and research in university settings and offers ways to integrate research into pedagogy. This book is a go-to reference for trainers and a hands-on guide for academics, researchers, and postgraduate students specialising in translation and interpreting curriculum development and pedagogy research.
1.Introduction: mapping the research landscape of translator and interpreter education (2001-2022) 2.Market needs analysis 3. Conceptualisation of content 4.Learning needs analysis 5.Goal and objective 6.Belief/philosophy 7.Syllabus/curriculum design and analysis 8.Material development 9.Instruction and/or effect 10.Assessment 11.Course/curriculum evaluation 12.Other research themes and their sub-themes
Keywords: Translating and interpreting -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting; EDUCATION / Research